Rancang Bangun Sistem Deteksi Kecepatan Kendaraan di Wilayah Zona Selamat Sekolah (ZoSS) Berbasis Mini PC - Desprijon Desprijon; Rahmi Eka Putri; Nefy Puteri Novani (Universitas Andalas, 2021)
This study aims to create a system to detect vehicle speed in the School Safe Zone area using Mini PC based with Computer Vision technology and Image Processing techniques. This research, was hoped for the drivers will more discipline in driving, so can create safe and comfortable traffic in the School Safe Zone area. This system was made using a camera module to take video of the track, Raspberry Pi was used as the main device for detection and speed calculation. Every vehicle which crossed the zone would be detected and tracked to follow every vehicle movement, then was conducted a process of saving the center point of the vehicle object based on the initial detection line. Finally, calculated the vehicle speed based on the distance and time the vehicle moved on the frame which was set based on the detection line. The results of the vehicle speed would be displayed on the LCD and the output was in the form of a sound from the speaker as a warning for drivers whose vehicle speed exceeds 25 km / hour. Based on results of this research, the system was capable for work well in detecting and getting the speed results of passing vehicles. However, for direct implementation the devices in this system are inadequate for video processing, so that the response time and accuracy level was obtained by the system did not match for actual conditions.